ANALYSIS OF THE DEVELOPMENT OF CHILDREN WITH SPECIAL NEEDS IN INCLUSIVE EDUCATION IN KINDERGARTEN - Isnaini, Indri Dwi; Fitri, Norma Diana; Ariyanti, Mira Pradipta (Universitas Al-Hikmah Indonesia, 2024)
A child who has special needs (ABK) needs appropriate education from an early age, considering that during this period there is an acceleration in the growth and development process. In line with that, inclusive education is present to answer this problem. Through this inclusive education, a child who has special needs (ABK) is able to learn, interact and play activities with other ordinary children to improve their development. This research aims to find out how the development of ABK when attending an inclusive school. This research answers this problem with a case study using a qualitative approach. Regarding methods, this research utilizes three data collection tools, namely observation and interviews, as well as documentation to answer questions more comprehensively. Based on the research results, it can be concluded that children with special needs can optimize their development in inclusive education which accommodates and facilitates children with special needs with special assistance to participate in learning and playing at school with other regular children. So that Children with Special Needs (ABK) can attend school comfortably and happily in inclusive schools. This is proven by the existence of a regular form of mutual respect between children towards a child who has special needs. So that a child who has special needs feels valued and confident in an inclusive school environment.